Study on the Analysis and Optimization of Starting Control Strategy of Wet Dual Clutch Transmission - Bingyu Zhang (Jixie chuandong)
Through building the dynamics model of the wet dual clutch transmission， and analyzing the starting control strategy， a method of dynamically adjusting the starting target speed is proposed. Used vehicle jerk and sliding friction work as the evaluation criteria， the starting smoothness is improved when meeting the dynamic response of vehicle starting. A wet dual clutch transmission of GERTRAK is used for verification， the result shows this way can improve vehicle starting quality.